Direct detection of spin polarization in photoinduced charge transfer through a chiral bridge. Issue 41 (11th October 2022) - Privitera, Alberto; Macaluso, Emilio; Chiesa, Alessandro; Gabbani, Alessio; Faccio, Davide; Giuri, Demetra; Briganti, Matteo; Giaconi, Niccolò; Santanni, Fabio; Jarmouni, Nabila; Poggini, Lorenzo; Mannini, Matteo; et al.
Abstract : Our work provides a first attempt to directly detect the spin polarisation of Chiral-Induced Spin Selectivity (CISS) effect by studying the photoinduced electron transfer in a CdSe Quantum Dot-chiral bridge-fullerene derivative (QD–χ–C60 ) system. Abstract : It is well assessed that the charge transport through a chiral potential barrier can result in spin-polarized charges. The possibility of driving this process through visible photons holds tremendous potential for several aspects of quantum information science, e.g., the optical control and readout of qubits. In this context, the direct observation of this phenomenon via spin-sensitive spectroscopies is of utmost importance to establish future guidelines to control photo-driven spin selectivity in chiral structures. Here, we provide direct proof that time-resolved electron paramagnetic resonance (EPR) can be used to detect long-lived spin polarization generated by photoinduced charge transfer through a chiral bridge. We propose a system comprising CdSe quantum dots (QDs), as a donor, and C60, as an acceptor, covalently linked through a saturated oligopeptide helical bridge (χ) with a rigid structure of ∼10 Å. Time-resolved EPR spectroscopy shows that the charge transfer in our system results in a C60 radical anion, whose spin polarization maximum is observed at longer times with respect to that of the photogenerated C60 triplet state. Notably, the theoretical modelling of the EPR spectra reveals that the observed features may be compatible with chirality-induced spin selectivity, but the electronic features of the QD do not allow the unambiguous identification of the CISS effect. Nevertheless, we identify which parameters need optimization for unambiguous detection and quantification of the phenomenon. This work lays the basis for the optical generation and direct manipulation of spin polarization induced by chirality.